Pengaruh return on assets, non performing loan, dan loan to deposit ratio terhadap capital adequacy ratio pada bank konvensional di Indonesia - Marlim, Francis; Setyawan, Ignatius Roni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
Capital adequacy ratio becomes an indicator to assess the good performance of a bank, in carrying out its business activities every bank will strive to generate optimal capital. The purpose of this study is to analyze the effect of profitability, asset quality, and liquidity on capital and theory that can explain the reasons banks need big capital. The population in this research is several 20 groups of conventional bank book 1 until book 4 from 2011 to 2016 in the Indonesia Stock Exchange. Analysis using the panel regression with the Generalized Least Square (GLS) method is used to test their hypothesis. The analysis finds that the first return on assets has a relationship to the capital adequacy ratio significantly on banking companies. Second, non performing loan have a relationship to the capital adequacy ratio significantly on banking companies. Third, loan to deposit ratio have a relationship to capital adequacy ratio significantly on banking companies. Based on the results, the researcher suggests doing more research on the other variables to have another model.